Sex Differences in Behavioral Circadian Rhythms in Laboratory Rodents - Krizo, Jessica A.; Mintz, Eric M. (Frontiers in Endocrinology, 2015)
There is a strong bias in basic research on circadian rhythms towards the use of only male animals in studies. Furthermore, of the studies that use female subjects, many use only females and do not compare results between males and females. This review focuses on behavioral aspects of circadian rhythms that differ between the sexes. Differences exist in the timing of daily onset of activity, responses to both photic and nonphotic stimuli, and in changes across the lifespan. These differences may reflect biologically important traits that are ecologically relevant and impact on a variety of responses to behavioral and physiological challenges. Overall, more work needs to be done to investigate differences between males and females as well as differences that are the result of hormonal changes across the lifespan.